Pengaruh Konservatisme Akuntansi Terhadap Biaya Ekuitas Dan Peran Komite Audit Sebagai Moderasi - Olvie Andellsi; Mayar Afriyenty (Universitas Negeri Padang, 2020)
This study was conducted to examine the effect of accounting conservatism on cost of equity capital and the role of the audit committee as moderation. This research is a type of causal associative research with quantitative approach. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018. Samples were selected using a purposive sampling method with a total sample of 280 samples. Cost of equity capital is measured using the Ohlson (1995) model. Accounting conservatism is measured by the Givoly and Hayn (2000) model. The role of the audit committee is measured through the experience and capabilities possessed in the field of accounting and finance. The results showed that accounting conservatism had a significant negative effect on the cost of equity capital. In addition, the role of the audit committee is able to moderate the relationship between accounting conservatism and the cost of equity capital. For further research is expected to expand the object and year of research because in this study only examined manufacturing companies for the 2014-2018 observation year. In addition, further research can look for other independent variables if you want to do the same research.